Survey and Literature Assessment on the Financial Literacy of University Students - Zéman Zoltán; Kálmán Botond Géza; Bárczi Judit; Zoltan Zeman; Калман Ботонд Гейзо (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2021)
Abstract. The financial culture of university students has been a research topic in the economic literature since the 1980s. However, its significance has grown during the past decade. It owes on the one hand to the 2008 crisis and its subsequent effects; recently, however, the crisis being induced by the COVID-19 pandemic has become the major reason. On the other hand, Industry 4.0 is affecting financial development, too. It is crucial that we know how effective educating finances is; a multitude of surveys satisfy this requirement. In this study the authors compare the results of their own research carried out in one such topic with data arising from the available literature. Their primary goal was to draw attention to the weight of the topic and their second objective was to highlight the importance of reviewing scientific literature.

Az egyetemi hallgatók pénzügyi kultúrája az 1980-as évek óta téma a gazdasági szakirodalomban. Jelentősége azonban az utóbbi évtizedben nőtt meg igazán. Ennek oka egyrészt a 2008-as válság és annak tovagyűrűző hatásai, napjainkban pedig a Covid-19 okozta krízis. A másik ok, hogy az Ipar 4.0 a pénzügyek fejlődésére is hatással van. A közoktatás és a felsőoktatás szerepe egyre fontosabb a pénzügyi tudás és készségek közvetítésében. Fontos tudnunk azt is, hogy a pénzügyek oktatása mennyire hatékony. Erre szolgálnak a különböző felmérések. Ebben a tanulmányukban a szerzők egy ilyen témában készült saját felmérésük eredményeit hasonlítják össze a szakirodalomban fellelhető adatokkal. Elsődleges céljuk az volt, hogy felhívják a figyelmet a téma fontosságára, másodlagos szándékuk pedig az, hogy felhívják a figyelmet a szakirodalom tanulmányozásának fontosságára.

Резюме. Фінансова культура студентів університету є темою в економічній літературі з 1980х років. Однак її значимість по справжньому тільки за останнє десятиліття зросла. Причиною цього є з одного боку, криза 2008 року та її наслідки, а у наші дні – криза, спричинена COVID-19. Інша причина полягає в тому, що Промисловість 4.0 також впливає на розвиток фінансів. Роль державної освіти та вищої освіти набуває все більшого значення у передачі фінансових знань та навичок. Важливо також знати, наскільки ефективна фінансова освіта, для чого служать різні опитування. У цьому дослідженні автори порівнюють результати власного опитування на таку тему з даними, знайденими в літературі. Їх основною метою було привернути увагу до важливості теми, а другорядним наміром – звернути увагу на важливість вивчення літератури.
Egyetemi hallgatók pénzügyi kultúrájának felmérése és szakirodalmi megítélése
Оцінка та огляд літератури щодо фінансової грамотності студентів університет
https://kmf.uz.ua/wp-content/uploads/2022/04/limes-2021-issue-viii_2021-12-30.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00009320
Keywords: financial literacy; university student; crisis situation; financial education